Ethnomedicine Knowledge Among Iranian Patients With Gastrointestinal And Liver Disorders: A Cross-Sectional Study - Fatemeh Sadat Hasheminasab, MD,Ph.D; Yasaman Zamanian, MD; Saiedeh Haji-Maghsoudi, Ph.D; Alireza Bakhshipour, MD; Maryam Azimi, MD,Ph.D (Current Therapeutic Research)
Introduction: The role of complementary and alternative medicine (CAM) in healthcare is substantial and frequently overlooked, with widespread use in both developed and developing countries. This study aimed to explore the ethnomedicinal knowledge including prevalence, socio-demographic, and health related characteristics related to gastroenterology and hepatology disorders in Kerman province. Materials and methods: This study included 400 eligible patients attending gastroenterology and hepatology outpatient clinic. Data collection was conducted using various assessment tools, that is, a self-administered demographic and ethnomedicine questionnaire, and quality of life questionnaire. Results: The findings of the present study revealed that 40.3% of the patients surveyed commonly used CAM. Among the participants, 63.4% did not alter their medication intake while using CAM, and 85.7% were satisfied with its effectiveness. The majority of consumers relied on friends and family, making up 41.6% of the sources of information on CAM, with only 14.9% disclosing their CAM usage to physicians. Furthermore, CAM users have a significantly higher level of education, with the physical functioning being a key aspect of QOL. Conclusion: Although the results of this study may not be broadly generalizable, specific points in the findings are still significant. The utilization of CAM treating for gastrointestinal and liver issues is becoming more prevalent among patients in the area. It is essential to educate patients about the real effects of CAM in disease prevention and treatment, particularly considering patient concerns about side effects, and untrustworthy information sources.